Marsupialization is the optimal treatment for odontogenic keratocyst in pediatric patients. Issue 1 (April 2019) - Harada, Kyoko; Nagata, Sachiko; Shiraishi, Aiko; Shinonaga, Yukari; Iseki, Tomio; Arita, Kenji
Abstract: Odontogenic keratocyst (OKC) shows a high rate of recurrence, so aggressive treatment has been recommended. However, if the patient is a child and still has unerupted permanent teeth in the region of the OKC, aggressive treatment may not be the best option. We report herein a case of multiple OKCs in a pediatric patient treated using marsupialization five times and enucleation twice. Recurrence was not observed after surgical treatments in 7 years of follow-up. We suggest that treatment with marsupialization should be considered as the first-line treatment strategy for young patients with OKC.